TINGKAT MATHEMATICS ANXIETY PADA MAHASISWA CALON GURU MATEMATIKA - Rizta, Amrina; Antari, Luvi (Mathematics Education Journal, 2019)
This study is qualitative research that aims to determine the level of mathematics anxiety (MA) in prospective mathematics teacher at the Muhammadiyah University of Palembang. Subject of this study is 58 college students. This research use qualitative descriptive method. The data collection process are observation, questionnaire, and interview. Based on the research that has been carried out it is known that the most dominant criteria for mathematical anxiety are anxiety about mathematical tests and anxiety about mathematical assignments and numerical calculations. The cognitive domain includes: often feel worried when given questions by the lecturer suddenly, difficulty remembering and using mathematical procedures. The attitude domain includes: fear of not being able to answer questions from friends and not confident in doing the tasks given and transferring the knowledge that has been obtained. In the somatic domain include: heart pounding when the lecturer holds a quiz suddenly, feeling nauseous and suddenly dizzy when presenting the task in front of the class. In the mathematical representation domain includes: difficult to do math problems correctly and quickly because they do not understand the purpose of the problem and it is difficult to interpret words that are words into mathematical sentences.DOI: 10.22342/jpm.13.1.6827.9-20